When Waiting Saves Myocardium: Deferred stenting in a 30-year-old STEMI Patient - Astri Meliana Meliana; I Putu Gede Budiana; I Dewa Agung Gede Oka Dwi Wicaksana (Universitas Pahlawan Tuanku Tambusai, 2026)
Acute coronary syndrome (ACS) is one of the manifestations of cardiovascular disease (CVD) that often occurs in patients. The ST-elevation myocardial infarction (STEMI) was the most common of ACS manifestations and showed high mortality rates. Therefore, adequate treatment is required. The primary PCI remains a gold standard in STEMI management, as it significantly improves clinical outcomes by restoring coronary blood flow and preserving jeopardized myocardium. A 30-year-old male patient presented with chest pain 5 hours ago. The pain was located in the mid-sternal area of the chest and radiated to the back. The symptoms developed after the patient had finished playing futsal. The patient denied other associated symptoms such as shortness of breath. The ECG showed ST-elevation in V1-V6 leads and high hs-troponin marker. The patient was diagnosed with an extensive anterior ST-elevation myocardial infarction. On coronary angiography examination, the patient was resulted with high thrombus burden. Moreover, the patient was treated with initial pharmacological medications and primary PCI, particularly the plain old balloon angioplasty (POBA) with deferred stenting. On the sixth day of hospitalization, the patient had a stable condition and was discharged from the hospital. The primary PCI with POBA and deferred stenting can be considered as an alternative treatment approach in STEMI with HTB patients.